Factors affecting COVID-19’s mental health impact on college students in the southeastern United States - Chenneville, Tiffany; Gabbidon, Kemesha; Zharima, Campion; Hornschuh, Stefanie; Dietrich, Janan Janine (Frontiers in Public Health, 2023)
Emerging evidence confirms COVID-19's negative impact on college students' mental health; however, more research is needed to identify factors that promoted or hindered college students' mental health early in the pandemic. This exploratory study addressed this need. Participants were 697 students attending a large, state, urban university in the southeastern United States (US). Using a cross-sectional survey design, participants completed an anonymous, online survey assessing socio-demographic variables, mental health issues, and activities during the lockdown period in 2020. Findings suggest college students in the southeastern US who were women or transgender men and had pre-existing mental health conditions, fewer routine activities, and high exposure to COVID-19 news reported more mental health problems early in the pandemic. Students who exercised daily had fewer symptoms of anxiety and post-traumatic stress than students who exercised monthly, but there were no differences in emotional responses to COVID-19 based on exercise frequency. Tailored strategies to address college students' needs in response to the current or future pandemics are needed and should take into consideration factors that promote or hinder mental health. Patient or Public Contribution: College students were participants in this study. College students who were not participants in this study assisted with the implementation of this study.